Antibacterial Activity of Surfactin and Synergistic Effect with Conventional Antibiotics Against Methicillin-Resistant Staphylococcus Aureus Isolated from Patients with Diabetic Foot Ulcers [Response to Letter] - Li Z (Diabetes, Metabolic Syndrome and Obesity, 2023)
Zhaoyinqian Li1–3 1Department of Laboratory Medicine, the Affiliated Hospital of Southwest Medical University, Luzhou, People’s Republic of China; 2Sichuan Province Engineering Technology Research Center of Molecular Diagnosis of Clinical Diseases, Luzhou, People’s Republic of China; 3Molecular Diagnosis of Clinical Diseases Key Laboratory of Luzhou, Luzhou, People’s Republic of ChinaCorrespondence: Zhaoyinqian Li, Email lizhaoyinqian@swmu.edu.cn